Laparoscopic Assisted Transmesocolonic Percutaneous Nephrolithotripsy in Ectopic Iliac Kidney - N. Sohail; A. Albodour; K. Abdelrahman (Urology Case Reports, 2016)
We report a case of 15-year old female who presented with recurrent lower abdominal pain treated three times with ESWL previously. She was diagnosed as having right ectopic kidney with a 4 cm renal stone in renal pelvis and involving lower and mid calyx. She was treated successfully with laparoscopic assisted transmesocolonic percutaneous nephrolithotripsy. Procedure resulted in complete stone clearance without any perioperative or post operative complication. Patient stayed in hospital for 72 h with no drains or stents after day 5, post operatively.